Accelerated oxidation behavior of NbSi2 coating grown on Nb substrate at 600-900 degrees C - Yoon, Jin-Kook; Kim, Gyeung-Ho (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Isothermal oxidation of NbSi2 coating formed on Nb substrate was investigated in air at 600-900 degrees C, which exhibited the complex and accelerated kinetics at intermediate temperatures and failed due to either the cracking of the NbSi2 coating or the oxide layer formed. This complex oxidation behavior was governed by the balance between the stress generated by the forming of oxide phases and the subsequent stress relaxation processes. Pesting-induced accelerated oxidation at 700 degrees C was affected by extrinsic factors such as pre-existing defects in NbSi2 coating. Accelerated oxidation originated from the oxide layer cracking at 750 degrees C was intrinsic to NbSi2.
Keywords: IN-SITU COMPOSITES; TEMPERATURE OXIDATION; NIOBIUM; MOSI2; RESISTANCE; AL; MICROSTRUCTURE; KINETICS; PEST; MO